Not “just a bad period”— The impact of a co-created endometriosis social media health campaign: a mixed methods study - Stanek, Ditte Bonde; Hestbjerg, Ida; Hansen, Karina Ejgaard; Tomlinson, Maria Kathryn; Kirk, Ulrik Bak (Frontiers in Communication, 2023)
Objective: The goal of this study was to evaluate the impact of a visual social media health campaign. The #1in10 campaign was co-created by the Danish Endometriosis Patient Association and women with endometriosis. Methods: Seven semi-structured interviews were conducted with campaign participants to evaluate their experience of participating. The interviews were then analyzed thematically. Social media metrics on the reach of the campaign were gathered to assess how the campaign had performed. Results: Seven themes were identified in the interviews: (1) Taboo, (2) Visibility, (3) Awareness, (4) Acknowledgement, (5) Empowerment, (6) Patient Experts, and (7) Community. Throughout the interviews, the women conveyed that they found their participation in the campaign meaningful, as it contributed to creating awareness and recognition of a disease otherwise surrounded by taboo and stigma. Social media metrics show how the #1in10 campaign reached both people inside and outside the endometriosis community. Across the FEMaLe Project’s three social media platforms, 208 (51,5%) of engagements were with patients with endometriosis, 96 (23,7%) were with FEMaLe employees and advisers, 94 (23,3%) were with the general public, and 6 (1,5%) were with policymakers. In the month the #1in10 campaign was released, the FEMaLe Project’s Twitter and Instagram accounts had more impressions than almost any other month that year (except January on Twitter and November on Instagram). The FEMaLe Project’s LinkedIn had the same number of impressions as in other months. Discussion: The study shows that the #1in10 social media campaign had an impact on three levels: on an individual level for the participating patients, on a communal level for people with endometriosis, and on a wider societal level. The participating patients felt empowered by their involvement with the campaign and the act of coming forward. The participants acted on behalf of their community of people with endometriosis, in the hopes that it would raise awareness and acknowledgment. In return, the community engaged with the campaign and added significantly to the dissemination of its message. On a societal level the campaign has caught particular attention and engagement compared to other posts made on the same social media accounts.